Sensitive detection of tumor mutations from blood and its application to immunotherapy prognosis - Shuo Li (Nature Portfolio, 2021)
It is possible to call single-nucleotide variant (SNV) in cell-free DNA (cfDNA), but the accuracy of detection is often affected by low tumour cfDNA content. Here, the authors develop a method, cfSNV, and show that it can be used even for medium-coverage whole exome sequencing of cfDNA.